Statistic analysis of thunderstorm characteristics in Guangxi in 2022 - Huali WU; Bingfu LU; Yaoling ZHI; Kuan HE; Dan HUANG; Xiaoyan CHEN (暴雨灾害, 2024)
In order to improve the understanding of the characteristics of thunderstorms in Guangxi and better study its forecasting methods, based on the 2022 VLF/LF 3D lightning data and SWAN radar 3D composite data, 1 131 thunderstorm cases were identified and extracted by integrating SCIT (Storm Cell Identification and Tracking) and DBSCAN (Density Based Spatial Clustering of Applications with Noise), and thunderstorm feature data sets were constructed. Based on this data set, statistical analysis was carried out on the characteristics of thunderstorms in Guangxi, such as the spatiotemporal distribution, movement direction, duration, movement speed, and movement distance. Then further analyze the distribution characteristics of radar reflectivity, vertically integrated liquid water (VIL), and echo height in thunderstorm environments. The results are as follows. (1) Thunderstorms in Guangxi are characterized by more in the south and less in the north, with the highest thunderstorm activity in the southern coastal areas. Thunderstorms occur most frequently in summer (June-August), accounting for 65.3%, while they sharply decrease in winter (December-February), accounting for only 0.18%. Thunderstorms mainly occur from 11 ∶00-19 ∶00 BT during the day. (2) The thunderstorms speed was mainly concentrated in the range of 2~16 m·s-1, with the most frequent speed being 4~6 m·s-1. The movement distance was mainly within 100 km, with the most frequent distance being 10~20 km.The dominant movement directions of the thunderstorms were northeast, north, northwest, and east. There are certain differences in both speed and distance among thunderstorms moving in different directions. Specifically, thunderstorms moving eastward tend to be faster (8~16 m·s-1) and travel farther (10~40 km), those moving southward are generally slower (2~10 m·s-1) and travel shorter distances (0 to 30 km); thunderstorms moving in other directions have speeds concentrated 4~12 m·s-1, though with varying peak ranges. (3) The initial flash in thunderstorms often occurs in areas with reflectivity greater than 45 dBz and VIL less than 30 kg·m-2. Lightning after the initial flash is primarily occurs in the 45~65 dBz strong echo region and is highly correlated with VIL in the range of 0.1~40 kg·m-2. The strong echo core which threshold greater than 45 dBz with top height exceeds 6 km can be used as one of the reference indicators for lightning occurrence.